Aidina and Tamyiz Program At Ocean Arabic Language Course Institution in Controlling And Evaluation/ Pengawaasan dan Evaluasi Program Aidina dan Tamyiz di Lembaga Kursus Bahasa Arab Ocean - Sakinah Naziha; Bahrul Ilmi; Zakiyah Arifa (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
Monitoring and evaluation are critical to see the success of an Arabic language program. This study aims to reveal the monitoring and evaluation process carried out at the Ocean course institute. This research uses a descriptive qualitative approach. The primary data source for this research is the results of interviews with Ocean's founders, teachers, and students. In addition, the data will be supported by documents and scientific articles to strengthen research results. All data was obtained through observation techniques, interviews, and documentation. The data were analyzed by collecting, reducing, presenting, and drawing conclusions. Researchers carried out triangulation to ensure the validity of the data by comparing all the data that had been obtained. The results of this study are, (1) the form of controlling carried out by Ocean on the Aidina and Tamyiz programs is inherent controlling which is preventive, repressive, active, and passive. Besides that, another form of control is functional controlling, which occurs in internal leadership because parties within the institution only supervise it. (2) the form of the evaluation carried out by the Ocean agency is an evaluation of inputs, processes, and results. In addition, Ocean also conducts formative and summative evaluations. Based on the evaluation results, the program has been appropriately implemented and has achieved its objectives. The evaluation of the Aidina and Tamyiz programs is focused on the extent to which students' ability to learn the material provided.Abstrak: Pengawasan dan evaluasi sangat penting dilakukan untuk melihat keberhasilan sebuah program bahasa Arab. Penelitian ini bertujuan untuk mengungkap proses pengawasan dan evaluasi yang dilakukan di lembaga kursus Ocean. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deksrptif. Sumber data primer dari penelitian ini adalah hasil wawancara dengan pendiri Ocean, guru, serta murid. Selain itu data akan didukung dengan dokumen dan artikel ilmiah untuk memperkuat hasil penelitian. Seluruh data didapatkan melalui teknik observasi, wawancara, dan dokumentasi. Data yang terkumpul dianalisis dengan tahapan pengumpulan, reduksi, penyajian, dan penarikan kesimpulan. Triangulasi dilakukan peneliti untuk memastikan keabsahan data dengan membandingkan seluruh data yang telah diperoleh. Hasil dari penelitian ini yaitu, (1) bentuk pengawasan yang dilakukan oleh Ocean terhadap program Aidina dan Tamyiz adalah pengawasan melekat yang bersifat preventif, represif, aktif, dan pasif. Selain itu bentuk pengawasan lainnya adalah pengawasan fungsional yang terjadi adalah pengawasan internal karena hanya diawasi oleh pihak dalam lembaga. (2) bentuk evaluasi yang dilakukan oleh lembaga Ocean adalah evaluasi masukan, proses, dan hasil. Selain itu Ocean juga melakukan evaluasi formatif dan sumatif. Berdasarkan hasil evaluasi, program telah dijalankan dengan baik dan mencapai tujuan yang ada. Evaluasi program Aidina dan Tamyiz dititik beratkan pada sejauh mana kemampuan siswa belajar materi yang diberikan